THE ROLE OF NURSES IN IUD INSERTION: AN ANALYSIS OF THE EVOLUTION IN CAMPO GRANDE/MS BETWEEN 2019 AND 2023 - de Lima, Anaísis Araújo; Ricci, Ana Patrícia (Seven Editora, 2025)
Family planning is a right guaranteed by law and fundamental for individuals to be able to make informed decisions about their reproduction. In Brazil, the Unified Health System (SUS) plays a crucial role, offering access to contraceptive methods, including Intrauterine Devices (IUDs), which are long-acting reversible methods (LARC) with high efficacy. The copper IUD, for example, is valid for up to 10 years and is 99% effective. The insertion of the IUD can be performed by both doctors and trained nurses, a practice regulated by the Federal Nursing Council (COFEN), expanding access to this method, especially in regions with a shortage of doctors. In Campo Grande (MS), training programs have trained nurses to insert IUDs, contributing to an increase in insertions, especially with the performance of resident nurses in the TEIAS project. This study aims to analyze the number of IUD insertions performed by physicians and nurses, highlighting the fundamental role of nurses and residency programs in promoting family planning in Primary Health Care. The research is quantitative, based on secondary data from the Health Information System for Primary Care (SISAB) between the years 2019 and 2023. The results show the positive impact of IUD insertion by nurses in increasing access to contraceptive methods, reflecting the progress in reproductive planning in the SUS. DOI: https://doi.org/10.56238/sevened2024.037-186